Chemopreventive alteration of the cell-cell adhesion in head and neck squamous cell cancer - Naim, Ramin; Chang, Ray C.; Schultz, Johannes D.; Hörmann, Karl (Oncology reports, 2006)
Approximately 310,000 new cases of oral and pharynx cancer account for a major cause of neoplasm related morbidity and mortality world-wide. Unfortunately, the survival rate has not improved significantly in the last decade. The vast majority of head and neck cancer is squamous cell carcinoma. The major adhesion-proteins involved in the development and maintenance of all solid tissue are the Cadherins. Cadherins are the transmembrane components of the adherent junction with interaction with plakoglobin and β-catenin. Downregulation of Cadherins and catenins is frequently observed in many types of human cancer. Sulindac sulfone is one of the new therapeutic apoptotic agents that show promise in the treatment of cancer. In this study, we incubated sulindac sulfone with a head and neck cancer cell line and investigated the outcome of E-Cadherin. Immunohistochemical and Western blot analyses were then performed, with different concentrations of sulindac sulfone (100, 200, 400, 600, and 800 µMol) for 48 h. At 400 µMol of sulindac sulfone a decrease of 21% was observed; at 600 µMol, 44% decrease of β-catenin concentration was seen, and incubation with 800 µMol resulted in 73% reduction of secreted β-catenin. Incubation with sulindac sulfone seemed to stop proliferation; however, with respect to the controls, there was no increased reduction of the total protein. Sulindac sulfone resulted in an increase of E-Cadherin content in the head and neck squamous cell cancer cell line after 48 h of incubation; however, the reactivity was restricted to the adherent junctions. At increasing concentrations of sulindac sulfone, intercellular E-Cadherin immunostaining intensifyied. ELISA also depicted significant rising levels of E-Cadherin. Sulindac sulfone contributes to the inactivation of cGMP phospho-diesterase. Thus, the accumulation of cellular cGMP and protein kinase G is induced. The following degradation of the phosphorylated β-catenin and the dissociation from the Cadherin-catenin complex releases E-Cadherin. This may also contribute to growth inhibition and co-ordinate with apoptosis induction. It is not really clear as to, which pathway results in the elevation of the E-Cadherin proteins. However, in epithelial cancer cells, the Cadherin-catenin complex serves as a target for the chemopreventive agent, sulindac sulfone.